Bone density assessment for evaluation of gender differences in cervical vertebral maturation: A computed tomography study - K Usha; Balashanmugam Baskaranarayanan; D Nagarajan; R Selvarani; M Vijjaykanth (Wolters Kluwer Medknow Publications, 2016)
Introduction: The cervical vertebral maturation (CVM) method is a vital tool for assessing the biological maturation of the orthodontic patient to evaluate the amount of mandibular bone growth left. Aim: To assess and visualize the cervical vertebral morphology (bone density) of orthodontic patients of the age group 9,16,27 years. Material and Methods: Twenty four subjects with age group of 9,16,27 who were randomly selected and subjected to 3d tomographic study to estimate the biological age of the orthodontic patients by analyzing c1 c2 and c3 vertebrae. Result: The results showed that bone density of males is lesser than females in 9 and 16 years, whereas they have more bone density than females in 27 years. Conclusion: The study provides qualitative method of assessing the biological age of the patient by using images of cervical vertebrae by three dimensional approach. Hence it can be useful for orthodontic diagnosis and treatment plan.